Revisiting CGNet Swara and its Impact in Rural India - Marathe, Meghana; O'Neill, Jacki; Pain, Paromita; Thies, William; Thies, Bill (ACM - Association for Computing Machinery, 2015)
CGNet Swara is a voice-based platform for citizen journalism, launched in rural India in 2010. Since then, CGNet Swara has logged over 575,000 phone calls, over 6,900 published stories, and 287 reports of specific problems that were solved via the system. In this paper, we characterize the ongoing impact of CGNet Swara using a mixed-methods approach that includes 70 interviews with contributors, listeners, moderators, journalists, officials, and other factors. Our analysis also draws on the content of published posts, two focus groups, and a 9-day field immersion. Our results highlight personal narratives of the transformative benefits CGNet Swara has brought to rural communities. While the resolution of grievances is the most visible impact, we also uncover a diverse portfolio of other impacts connected to contributing and listening to the platform, as well as opportunities to further enhance impact. Our work contributes to the dialogue surrounding the impact of ICTD projects, especially those that span multiple years.